1978
DOI: 10.1088/0022-3727/11/13/010
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of ionisation growth in gas mixtures

Abstract: Ionisation growth in the gas mixtures, N2:NO, N2:He and CO2:N2:He has been studied using combined spatial and temporal measurement techniques. Observations in N2:NO mixtures confirmed that reliable information about primary ionisation processes could be obtained even in the presence of large secondary surface ionisation processes and extensive studies of the two ternary mixtures CO2:N2:He (1:1:8) and (1:2:3) and one binary N2:He (1:9) mixture have been undertaken. Primary and secondary ionisation coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Lakshminarasimha et a1 (1976) and Haydon and McIntosh (1978) have shown that the ionisation rate is highly dependent on the gas composition in C02:N2:He gas mixtures.…”
Section: The Electron Drift Velocitymentioning
confidence: 99%
“…Lakshminarasimha et a1 (1976) and Haydon and McIntosh (1978) have shown that the ionisation rate is highly dependent on the gas composition in C02:N2:He gas mixtures.…”
Section: The Electron Drift Velocitymentioning
confidence: 99%
“…The temporal growth of the ionisation current was measured by chopping the uv lamp and observing the resultant current waveform (see e.g. figure 1, Haydon and McIntosh 1978). The current decay was measured after the lamp had been switched off, to avoid complications from the start-up transient after the lamp was switched on.…”
Section: 2 Temporalmentioning
confidence: 99%